Modelling an idle building case through SWOT analysis and Fuzzy DEMATEL: a study on anti-commons - Filipe, J. A.; Genç, T. (European Research Studies Journal, 2019)
The situation of buildings degradation is very severe in many cities in the world. The case of a degraded building is studied in this article. The building becomes ruined because owners do not agree about what to do with the building and no one can use it without the consent of the others. Besides, time makes the building become with a lower value. After a long period of degradation, the question “what doing now?” is posed. Considering the situation of many degraded buildings, the present study aims to analyze a possible cause and work a situation of anti-commons concerning a building owned by several holders having each one exclusion rights. We use SWOT Analysis to build strategies for this anti-commons’ real estate case. Then Fuzzy DEMATEL model is applied to understand the relations between strategies for a final decision. Conclusions allow understanding the relations between strategies and how they influence each other to get a final decision for this problem. For our case, we recommend a concrete strategy to the owners after evaluating the preferences of the decision makers.